Urine alpha1-microglobulin is a better marker for early tubular dysfunction than beta2-microglobulin among tenofovir-exposed human immunodeﬁciency virus-infected men who have sex with men - Kang,Jing (2015)
Objectives: Men who have sex with men are at risk of tenofovir nephrotoxicity due to its wide use in both treatment and prophylaxis for human immunodeﬁciency virus infection, but little is known about the urinary biomarkers of early renal dysfunction in this population. This study aims to identify useful biomarkers of early renal dysfunction among human immunodeﬁciency virus-infected men who have sex with men exposed to tenofovir.Methods: In a cross-sectional study urinary alpha1-microglobulin, beta2-microglobulin, N-acetyl-B-n-glucosaminidase and albumin were measured and expressed as the ratio-to-creatinine in 239 human immunodeﬁciency virus-infected men who have sex with men who were treatment naïve or receiving antiretroviral therapy with tenofovir-containing or non-tenofovir-containing regimens. Additionally, 56 patients in the non-antiretroviral therapy group started a tenofovir-containing regimen and were assessed after 3 and 6 months on antiretroviral therapy.Results: Both the frequency of alpha1-microglobulin proteinuria (alpha1-microglobulin-creatinine ratio >25.8 mg/g) and the median urinary alpha1-microglobulin-creatinine ratio were higher in the tenofovir disoproxil fumarate group than the other two groups (all p< 0.05). A higher frequency of beta2-microglobulin proteinuria (beta2-microglobulin-creatinine ratio >0.68 mg/g) was also observed in the tenofovir group (28.9%) compared to the non-tenofovir group (13.6%, p= 0.024). There were no signiﬁcant differences between groups for N-acetyl-β-n-glucosaminidase and albumin. In the longitudinal study, the median urinary alphat-microglobulin-creatinine ratio after 3 and 6 months on tenofovir-containing therapy (16.8 and 17.3 mg/g) was higher than baseline (12.3 mg/g, p= 0.023 and 0.011, respectively), while no statistically important changes were observed in urinary beta2-microglobulin-creatinine ratio or in the other biomarkers after 3 and 6 months on antiretroviral therapy (all p> 0.05).Conclusion: Urinary alphat-microglobulin seems to be a more sensitive and stable indicator of tubular dysfunction than urinary beta2-microglobulin for assessing tenofovir-related nephrotoxicity and can be signiﬁcantly altered after tenofovir exposure.